Analisis Manajemen Usaha Ternak Babi Di Bptuhpt Siborong-Borong - Masadjie Syahputra; Rifki Fahrizi; M. Ichsan Dicky Hermawan; Muhammad Khairan Hakim; Kiagus Muhammad Zain Basriwijaya (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to analyze pig farming with 7 livestock management. The research was conducted on November 9, 2024. The research This research uses qualitative data. The data obtained then analyzed descriptively to describe the state of the business and livestock management. management of the farm. The results of the study showed that the selection of superior seeds,efficient feed management, cage management, proper harvest management and determination of the ideal slaughtering time and overall marketing strategy and the overall marketing strategy is the success of pig farming by achieving high productivity and sustainable profitability. continue.